Climate change distress and impairment among adolescents in Germany - König, Lars; Schröder, Rebekka; Breves, Priska; Linnemann, Gesa Alena; Hamer, Tim; Suhr, Ralf (Frontiers in Climate, 2025)
IntroductionClimate change is one of the most consequential challenges in the 21st century with widespread consequences, including its effect on mental health. A recently developed questionnaire distinguishes between the affective responses to climate change, including negative emotions (distress), and functional impairments. Adolescents are considered particularly vulnerable but have not yet been studied concerning these dimensions. This study investigates the prevalence and distribution of climate change distress and impairment and their association with sociodemographic factors and health literacy in a representative sample of adolescents living in Germany.Materials and methodsIn a cross-sectional quota-based survey, N = 1,021 adolescents (inclusion criteria: age 12–17 years, enrollment in school, living in Germany, sufficient German knowledge) completed an online or face-to-face interview assessing the climate change distress and impairment scales (CC-DIS), sociodemographic information and a health literacy questionnaire (HLS-EU-Q16). ANOVAs and t-tests were used to analyze differences between sociodemographic groups and different levels of health literacy.ResultsThe results show that many adolescents are both distressed and impaired by climate change. Higher distress was found in girls vs. boys, those with high vs. low levels of education and high social status vs. lower social status. Higher impairment was found in girls vs. boys, 14–15-year-olds vs. 12–13-year-olds and 16–17-year-olds, those with low vs. high levels of education, and those with inadequate and problematic vs. adequate health literacy.DiscussionFurther research is needed to explore the underlying mechanisms and develop effective strategies to support adolescent mental health in the face of climate change.